A imagem das adolescentes na web: a busca pela corporeidade espetacular - Almeida, Mariane Tojeira Cara (2013)
Since the beginning of the twentieth century, the teenagers use interpersonal communication resources mediated for sociability purposes, having as first mean the wire line telephone, which lasted until the end of the 1990 s. In the early 21th century, with the advent of social networking, the body invisibility of the wire line telephone was supplanted by extra-visibility of digital photos posted on personal pages. These are images worked in details in order to present spectacular bidimensionalized corporeality. This is the object of this research that aims to analyze, from a semiotic point of view, these images that, far from simple capture of the anatomic-physiologic body arise, present, in fact, the Ideal I emulated in media images. The selection of the corpus of pictures focused on images of teenagers, because these are subjects who experience a peculiar biological stage, at a time when the body undergoes changes of puberty, surrendering to image editing, either it in stage of pre-production, production, or post-production. The conceptual frameworks first by understanding youth passes while class invented in the 19th century, highlighting the main Latin American theorists that study on the subject and reinforce the relevance of the media to the juvenile temporal clippings from the early 1950. Regarding the photographic images, bring to light the texts of Vilem Flusser, Roland Barthes and Lucia Santaella. By handling bodily images highlighted by digital photo, Act was important to consider the Sigmund Freud´s concept of narcissism, Jacques Lacan's mirror stage and the selfconstitution of the subject by Michel Foucault. Supported in this theoretical framework, the research followed to the empirical application. It is based on a methodology composed by a quantitative survey examined statistically, followed by two qualitative analysis: the first discusses the content of sentences written by teens about the Act of editing images, and the second presents a set of photographs of users of social networks, studied by the bias of peircian semiotics. From this research it was concluded that when adolescent girls post their selfportraits in the network, they become despots about themselves, enabling and disabling the signs that they represent in order to receive the approval of friends by the comments and by acts of "enjoy". It proves that the spectacular corporeality is predominantly visual production of the objectified subject on disposed images, ready to meet the gaze of the other